ANALISIS PROMOSI OLEH INFLUENCER TERHADAP PELAKU JUDI ONLINE PERSPEKTIF MASLAHAH - Aidil (TAHKIM, 2025)
This study focuses on the impact of online gambling site promotion among affiliate marketers or influencers from the perspective of maslahah, so that people can be more aware and wise in receiving information related to online gambling. Referring to online gambling promotions that are not in accordance with the moral and ethical values ​​upheld by Islamic-based communities. This study uses a qualitative approach without direct interviews that can be done by analyzing the role of influencers in online gambling actors. The case study in this study takes examples of several cases of promotion carried out by online gambling site influencers that are widely published and get public or media attention. The data sources used in this study come from questionnaires and literature studies. The data obtained are then classified, reduced, validated and presented through conclusions. The results of the study show that promotions carried out by influencers have violated aspects of sharia economics. Maslahah is not reflected in online gambling events, so the actions of influencers who promote online gambling can be considered misleading. Keyword: promotion, influencer, online gambling, maslahah